Fresh Properties Characteristics and Compressive Strength of Fiber Self-Compacting Concrete Incorporated with Rice Husk Ash and Wire Steel Fiber - Prayuda, Hakas; Dwi Cahyati, Martyana; Monika, Fanny (International Journal of Sustainable Construction Engineering and Technology, 2020)
Self-compacting concrete (SCC) is one of the innovations in concrete technology to help constructors in the casting process in hard-to-reach locations and to reduce the possibility of pores. SCC can also be green concrete by mixing it with some waste material without reducing its strength. In this study, SCC uses two types of materials, namely rice husk ash and wire fiber to produce green concrete and increase strength. Several experimental activities were carried out to examine the fresh and mechanical properties of the compacting fiber concrete itself. Fresh properties testing performed consisted of L-Box Test, V-Funnel Test and J-Ring Test. Whereas the investigation on mechanical properties was carried out by testing the compressive strength at 7, 14 and 28 days. The total sample used in this study amounted to 180 samples with a diameter of 15 cm and a height of 30 cm. Variations in this study consisted of a proportion of a mixture of rice husk ash and wire fibers in concrete. The results of the fresh nature test revealed that the addition of rice husk ash and wire fiber in SCC with a certain ratio could be used and accepted as self-compacting concrete. Furthermore, the mechanical properties test results show that there is an optimal proportion of mixing of the two materials to achieve normal concrete compressive strength.